Commission-revenue maximization in a general equilibrium model of asset creation. - Hara, Chiaki (Journal of Economic Theory, 1995)
Part of a special issue on financial innovation and security design. A general equilibrium model of endogenous asset formation is presented in which a monopolistic agent, called the designer, can create any types of assets and charge commissions as long as the total number of the types of assets is not greater than some given constant. The notion of an abstract cone is introduced in order to give the precise meaning to the limit of a sequence of budget sets. An existence theorem for the case where the designer can create no more than two assets is presented. The first of the two reasons for nonexistence of a commission-revenue maximizer is provided, and a nonexistence example is given for the case where the designer can create four assets. In addition, a case where no upper bound is imposed on the numbers of types of assets but where the number of types is endogenously determined by the designer is examined. The second of the reasons for nonexistence is then explained.